Just a little different - Dobkin, Bonnie; Martin, Clovis (Chicago : Childrens Press, 1993)
A child relates how he and his best friend, who is in a wheelchair, are both alike and different.
1.5
K-3
Keywords: Friendship -- Fiction; People with disabilities -- Fiction; Friendship -- Fiction; Physically handicapped -- Fiction